Neurodegenerative Diseases 1996
DOI: 10.1007/978-1-4899-0209-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of APP Secretion by Apolipoprotein E3 and E4

Abstract: The apolipoprotein E isozyme, apolipoprotein E4, has been implicated as a risk factor for Alzheimer's disease. One reason for the increased risk may be that apolipoprotein E binds to the A@ peptide, but there may be other factors as well. We show that apolipoprotein E is a potent regulator of the secretion of amyloid precursor protein. In cultures of PC12 cells, nanomolar levels of apolipoprotein E3 induce a rapid decrease in the secretion of APP, being observable in 30 min. and stable over 24 hours. Apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We observed that ApoE4 was more effective than ApoE in the increase of APP endocytosis and decrease of s␣-APP. A previous report described ApoE3-increased and ApoE4-decreased s␣-APP in PC12 cells (Wolozin et al, 1996). Although PC12 is a neuronal cell line, the different ApoE4 effects could be derived from a difference in ApoER2 or X11␣/␤ level from that in N2a-APP cells.…”
Section: Discussionmentioning
confidence: 86%
“…We observed that ApoE4 was more effective than ApoE in the increase of APP endocytosis and decrease of s␣-APP. A previous report described ApoE3-increased and ApoE4-decreased s␣-APP in PC12 cells (Wolozin et al, 1996). Although PC12 is a neuronal cell line, the different ApoE4 effects could be derived from a difference in ApoER2 or X11␣/␤ level from that in N2a-APP cells.…”
Section: Discussionmentioning
confidence: 86%
“…The effects of apoE isoforms on APP metabolism have been investigated in several cell culture systems with inconsistent results on cellular APP and secreted sAPP and Aβ (Biere et al . 1995; Wolozin et al . 1996; Hass et al .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no published studies have measured Aβ40, Aβ42 or APP‐CTFs after the addition of exogenous purified apoE. Prior studies adding purified apoE to cells in culture only evaluated APP or sAPP (Wolozin et al . 1996; Hass et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations